Association of children's toothbrushing and fine motor skills: a cross-sectional study (2022)
Fine motor skills (FMS) allow for the control and coordination of the distal musculature of hands and fingers, a skill required to brush teeth. The objective of this study was to investigate the association between FMS and toothbrushing efficacy. This cross-sectional study included 42 low-income Latino children aged 5 to 9 years from Pasto, Colombia. Toothbrushing efficacy was determined by the children’s dental plaque Quigley-Hein Index (QH-I) mean-score difference from before and after toothbrushing. FMS were evaluated using the 5–15R parent evaluation, the spiral drawing Archimedes test, and a neurodevelopmental assessment of movements and prehension patterns during toothbrushing. A descriptive analysis was performed to assess the characteristics of FMS and children’s toothbrushing, and a generalized linear model was used to determine associations between these skills and toothbrushing efficacy. Eighty-six percent of the children had at least one difficulty with FMS, and in 7%, they interfered with daily activities. Fourteen percent presented a moderate pattern in the Archimedes test, and 43% had inefficient prehension patterns. Toothbrushing reduced the QH-I by a mean of 1.45 (SD = 0.78–2.12) (p < 0.001). Toothbrushing efficacy was only significantly associated with age (mean-difference = -0.315, 95%CI: -0.481 to -0.148, p < 0.001). FMS and toothbrushing efficacy were not significantly associated. Other components of fine motor control should be analyzed to understand the kinetics of toothbrushing.